Global Economic Prospects and the Developing Countries 1997 - World Bank (Washington, DC: World Bank, 2019)
The year’s report projects an increase in the growth rate of global output, with notable contributions from Sub-Saharan Africa, the developing countries of Europe and Central Asian, and East Asian countries. This report places special emphasis on the role of the “Big 5” developing and transition economies – China, India, Indonesia, Brazil, and Russia – in the future of the global economy. In addition to assessing the current state of the world economy, this report discusses the expansion of global production and the costs of making the transition to a more open economy